Social media effects on the academic performance of Nile University students - Mowafy, Gina (AUC Knowledge Fountain, 2018)
The Internet and in particular social media applications such as Facebook, YouTube and many others, are obviously “overtaking the world” and could be regarded as “a global consumer phenomenon” (Camilia, Ibrahim, & Dalhatu, 2013) . Social media usage is one of the most common activities among children, adolescents, and emerging adults nowadays. It offers today’s youth a portal for entertainment and communication and it is becoming one of the main platforms for accessing information and news. This aggressive adoption of social media among the younger generation could be attributed to their up to date knowledge of and comfort with the latest technology and the convenient accessibility to these social networking tools (Vorderer, 2016). This study aims to shed the light on the social media effects on the academic performance of university students in Egypt and aims to clarify to different stakeholders the relationship between the social media usage and academic performance and to harness full potential of social media. This study examines the role of social media in students’ academic endeavors and ultimately their academic performance through their reported perceptions and reflections. It also examines factors that might influence the nature of this relationship, and its tentative impact on the academic performance of Nile University undergraduate students. An explanatory sequential mixed method approach is employed in order to get both quantitative and qualitative data, the responses of 442 Nile university undergraduate student were collected and were scored, coded and inserted into SPSS, and were analyzed using multiple statistical descriptive and inferential statistical tests based on the research question and the nature of the data to be analyzed using frequency tables, crosstabs, Anovas, post hocs and t-tests. The findings of the study explains the perception of Nile university students of social media effects on their academic performance, and to what extend do they use social media for academic related purposes, and it explores the effect of the different academic majors, academic statues and gender on the social media usage perception and usage. Significant differences in the behavior of students from different academic majors and different academic status in perceiving and using social media emerged which might require further investigation.